The story of the amulet - Nesbit, E. (Edith), 1858-1924. (New York : Puffin Books, 1996)
Cyril, Robert, Anthea, and Jane rescue a magic sand-fairy from a pet-shop cage. The creature leads them to an amulet which has the power to take them back in time.
4.0
5-8
Keywords: Amulets -- Fiction; Fairies -- Fiction; Time travel -- Fiction; Charms -- Fiction; Fairies -- Fiction; Fantastic fiction